Strategic capabilities and export performance of Indonesian SMEs: An empirical investigation of technological capacity, network competence, and market knowledge - Augustie, Cindy; Bengana, Ismail; Mili, Khaled; Benmoussa, Mohammed Soufiane (International Journal of Innovative Research and Scientific Studies, 2025)
This study examines the impact of strategic capabilities on export performance among 174 Indonesian SMEs and investigates whether environmental uncertainty moderates these relationships. Drawing on resource-based view theory, we analyze how technological capacity, network competence, and market knowledge influence export success in emerging economies. Using PLS-SEM analysis, our findings reveal that all three strategic capability factors significantly enhance export performance, with market knowledge demonstrating the strongest effect (β = 0.434, p<0.05), followed by technological capacity (β = 0.383, p<0.05) and network competence (β = 0.271, p<0.05). Contrary to theoretical expectations, environmental uncertainty did not significantly moderate these relationships, suggesting that internal capabilities are more critical determinants of export success than adaptability to external conditions. Our model explains 67.4% of the variation in export performance, offering strong explanatory power. These findings provide valuable insights for Indonesian SMEs seeking to enhance their international competitiveness and for policymakers designing export promotion programs. This study contributes to international business literature by clarifying the relative importance of different strategic capabilities for SME internationalization in emerging economies.